Bureaucratic Corruption and Endogenous Economic Growth - Ehrlich, Isaac; Lui, Francis T. (Journal of Political Economy, 1999)
There Appears to be significant diversity in the incidence of bureaucratic corruption across countries at different stages of economic development and under different political and economic regimes. Little theoretical or empirical analysis has been offered, however, on the link between corruption, government, and growth. The paper attempts to fill the void through equilibrium models of endogenous growth. “balanced growth” is derived as a balancing act between accumulating human capital, which engenders growth, and accumulating political capital, which mainly assures bureaucratic power. The analysis focuses on the interplay between investment in these two types of capital and its implications for long‐term growth under alternative political regimes. Some propositions are tested and confirmed empirically.